2011
DOI: 10.1021/am200927q
|View full text |Cite
|
Sign up to set email alerts
|

Superhard Tungsten Tetraboride Films Prepared by Pulsed Laser Deposition Method

Abstract: Attempts to synthesize and/or theoretically predict new superhard materials are the subject of an intense research activity. The trials to deposit them in the form of films have just began. WB(2) (77 wt % WB(2) and 23 wt % WB(4)) and WB(4) (65 wt % WB(4) and 35 wt % WB(2)) polycrystalline bulk samples were obtained in this work via electron beam synthesis technique and, subsequently, used as targets for films preparation by the pulsed laser deposition method. The targets were irradiated by a frequency-doubled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 26 publications
(61 reference statements)
4
37
2
Order By: Relevance
“…In the ultra-short ablation of a large number of systems, as it is reported in literature [6][7][8]12,25], the presence of two different laser induced emissions can be distinguished: a first plasma (primary plume) lasting for few hundreds of nanosecond and characterized by the presence of electronic transitions of atomic and ionic emissions and a second one (secondary component or plume) starting after few microseconds and showing a typical black-body like emission spectrum. The emission produced by ultra-short laser ablation of the ZrB 12 target presents a particular characteristic, in fact, together with the primary and secondary plumes also a third emission of material is present.…”
Section: Plasma Analysismentioning
confidence: 84%
See 2 more Smart Citations
“…In the ultra-short ablation of a large number of systems, as it is reported in literature [6][7][8]12,25], the presence of two different laser induced emissions can be distinguished: a first plasma (primary plume) lasting for few hundreds of nanosecond and characterized by the presence of electronic transitions of atomic and ionic emissions and a second one (secondary component or plume) starting after few microseconds and showing a typical black-body like emission spectrum. The emission produced by ultra-short laser ablation of the ZrB 12 target presents a particular characteristic, in fact, together with the primary and secondary plumes also a third emission of material is present.…”
Section: Plasma Analysismentioning
confidence: 84%
“…Usually, thin films obtained by ultra-short PLD are formed by particles ranging from tens to hundreds of nanometers in diameter and no larger particles are present onto their surfaces [6][7][8]. Fig.…”
Section: Target and Films Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Deposited films may have a thickness from several nanometers to several micrometers. In the last years, certain success has been achieved in the pulsed laser deposition of superhard thin films of tungsten tetra-boride (WB 4 ) [28]. Obtained by the PLD method, thin films of WB 4 on the SiO 2 substrate, according to theoretical calculations, have very high Vickers hardness of 42-50 GPa [28].…”
Section: Introductionmentioning
confidence: 99%
“…The early established hP14-W 2 B 5 [9] was recently identified as hP12-WB 2 [10], which has a maximum measured hardness of 42.2 GPa [11]. First-principles calculations suggested that hP6-WB 2 was energetically more stable than the experimentally reported hP3-WB 2 [12] and could have the high hardness with a value of 43.8-47.4 GPa [13,14].…”
mentioning
confidence: 97%